Hyperinsulinemia is a probable trigger for weight gain and hyperphagia in individuals with Prader‐Willi syndrome - Frederick A. Kweh; Carlos R. Sulsona; Jennifer L. Miller; Daniel J. Driscoll (Wiley, 2023)
Abstract Objective Prader‐Willi syndrome (PWS) is the most frequently diagnosed genetic cause of early childhood obesity. Individuals with PWS typically progress through 7 different nutritional phases during their lifetime. The main objective of this study was to assess potential factors, particularly insulin, that may be responsible for the weight gains in sub‐phase 2a and their role in the subsequent increase in fat mass and obesity in sub‐phase 2b and insatiable appetite in phase 3. Methods Fasting plasma insulin levels were measured in children with PWS between the ages of 0-12 years and in age‐matched non‐PWS participants with early‐onset major (clinically severe) obesity (EMO) and in healthy‐weight sibling controls (SC). Results Participants with PWS in nutritional phases 1a and 1b had plasma insulin levels comparable to SC. However, the transition from phase 1b up to phase 3 in the PWS group was accompanied by significant increases in insulin, coinciding in weight gains, obesity, and hyperphagia. Only individuals with PWS in phase 3 had comparable insulin levels to the EMO group who were higher than the SC group at any age. Conclusions Elevated insulin signaling is a probable trigger for weight gain and onset of hyperphagia in children with Prader‐Willi syndrome. Regulating insulin levels early in childhood before the onset of the early weight gain may be key in modulating the onset and severity of obesity and hyperphagia in individuals with PWS, as well as in other young children with non‐PWS early‐onset obesity. Preventing or reversing elevated insulin levels in PWS with pharmacological agents and/or through diet restrictions such as a combined low carbohydrate, low glycemic‐load diet may be a viable therapeutic strategy in combating obesity in children with PWS and others with early childhood obesity.